Clinical, biochemical and histological correlations in a group of non-drinker subjects with non-alcoholic fatty liver disease - (:unkn) unknown (Universa Press, 2007)
The correlation between biochemistry, imaging-studies and histology is a matter of controversy in non-alcoholic fatty liver disease (NAFLD) and the major pathophysiology of non-alcoholic steatohepatitis (NASH) is still unknown. We aimed to perform a comparative analysis between clinical, biochemical and histological variables of NAFLD. One-hundred and five NAFLD patients (F/M : 51/54), were studied, all with no-alcohol intake. The groups were followed-up for six months. Necroinflammation and fibrosis were more severe in patients with diabetes (p = 0.002, and p = 0.0001, respectively). In comparing NAFL to NASH, plasma nitric-oxide and malondialdehyde levels were significantly higher (p = 0.05, for-both), and vitamin-E and-C levels were significantly lower in NASH (p = 0.002, and 0.001, respectively). The serum ferritin levels were higher in NASH patients (p = 0.016). While the ultrasonographic grade was significantly higher, the liver-spleen density gradient was significantly lower in NASH group (p = 0.017, and 0.005, respectively). Within a six month period, serum ALT levels dropped into the normal range in 23/76 (30.3%) patients and serum ALT in the 6th month correlated significantly with the severity of steatosis, inflammation and fibrosis in initial biopsy (p = 0.023, 0.035, 0.011, respectively). In conclusion, the probability of severe liver disease is higher in patients with elevated-ALT in NAFLD. Serum ferritin levels have some prognostic significance in liver damage and fibrosis. Overt diabetes is predictive of advanced fibrosis and inflammation. However impaired glucose-tolerance is not. The advice on diet and exercise for six months after diagnosis may be a good strategy in NAFLD. The patients with normal-ALT without hepatomegaly, morbid-obesity and diabetes seem to have a good prognosis, however some of these patients may still require liver biopsy.
Keywords: Insulin resistance; Lipid peroxidation; Non-alcoholic fatty liver disease; Non-alcoholic steatohepatitis; Serum transaminases